Gruenhage Games on Groups - Bell, Jocelyn; Clontz, Steven (Topology Proceedings, 2025)
Abstract. One of Gary Gruenhage’s earliest contributions to topology appeared in the form of a topological game called the W-game. His W-game has been played ever since, and in this paper we explore his original game and the proximal game, a game that was inspired by the W-game, in the context of topological groups.